The role of training and education for enhancing empathy among healthcare students: a systematic review of randomised controlled trials - Caroline Teggi Schwartzkopf; Renata Tolêdo Alves; Pedro C. Lopes; Julien Braux; Filomena Capucho; Célia Ribeiro (BMC Medical Education)
Abstract Background Empathy can lead to a better patient-professional relationship, and this skill that can be learned and trained, and the university is the ideal place to start this training. The aim of this systematic review is to assess whether training and education interventions have an impact on increasing empathy in health students. Methods The acronym PICOS was used to formulate the research question. A high-sensitivity search was made combining indexed terms, entry terms, and Boolean OR/AND in 9 databases, including grey literature and manual search of retrieved articles. Two researchers selected the studies based on previously established eligibility criteria. The risk of bias was verified using the RoB2 tool and a meta-analysis was performed using RevMan 5.4. Results The analysis included 30 studies in the qualitative synthesis and 20 studies that presented adequate data for the meta-analysis. An overall moderate effect on participants’ empathy was found after the intervention (standardized mean difference 0.45, 95% CI 0.25 to 0.65). However, heterogeneity was high (I2 = 79%). More than half of the studies were considered at high risk of bias. The results suggests that interventions can be effective in increasing empathy. Conclusion This topic has been in the spotlight in the area of health education in recent years. And more quality studies will be needed, as well as long-term evaluation of interventions to ensure the durability of empathy enhancement. Clinical trial number Not applicable.